Nano-scale insights regarding coke formation in zeolite SSZ-13 subject to the methanol-to-hydrocarbons reaction. Issue 4 (14th January 2022) - van Vreeswijk, S. H.; Monai, M.; Oord, R.; Schmidt, J. E.; Vogt, E. T. C.; Poplawsky, J. D.; Weckhuysen, B. M.
Abstract : A correlation between the micro- and nano-scale coking behavior of SSZ-13 was discovered with in situ / operando spectroscopy and atom probe tomography (APT), which allows for spatial reconstruction and analysis of relations between framework elements and carbon atoms. Abstract : The methanol-to-hydrocarbons (MTH) process, commonly catalyzed by zeolites, is of great commercial interest and therefore widely studied both in industry and academia. However, zeolite-based catalyst materials are notoriously hard to study at the nano-scale. Atom probe tomography (APT) is uniquely positioned among the suite of characterization techniques, as it can provide 3D chemical information with sub-nm resolution. In this work, we have used APT to study the nano-scale coking behavior of zeolite SSZ-13 and its relation to bulk coke formation on the macro-/micro-scale studied with operando and in situ UV-vis spectroscopy and microscopy. Radial distribution function analysis (RDF) of the APT data revealed short carbon–carbon length scale affinities, consistent with the formation of larger aromatic molecules (coke species). Using nearest neighbor distribution (NND) analysis, an increase in the homogeneity of carbon was found with increasing time-on-stream. However, carbon clusters could not be isolated due to spatial noise and limited clustering. Therefore, it was found that the coke formation in zeolite SSZ-13 (CHA) is reasonably homogeneous on the nano-scale, and is rather similar to the silicoaluminophosphate analogue SAPO-34 (CHA) but different in nano-scale coking behavior compared to previously studied zeolite ZSM-5 (MFI).